Focus on world-class research to benefit community, country - T.N., Alagesh (New Straits Times Press (M) Bhd., 2023)
UNIVERSITI Malaysia Pahang Al-Sultan Abdullah (UMPSA) has set its eyes on world-class research and innovation in the fields of engineering, and technology through creative techniques to benefit the community and the country.